Conception Rate In Ewes Having Different Number of Ovulating Follicle During The First Estrous Cycle After PGF2, Injection - M.Y Sumaryadi; Wasmen Manalu (Media Veteriner, 1996)
Forty sis ewes were used to study the effects of number of ovulating follicle on the conception rate during the first estrous cycle after PGF& injection. The experimental ewes were injected twice with PGF& to synchronize estrous cycle and to remove previously existed corpus luteum. The number of ovulating follicle was determined by counting the number of corpus luteum by laparoscopy, 5 days after the estrous cycle. The distribution of ewes having 1. 2. 3, and >3 ovulating follicle was 12, 19, 12, 3, respectively. Conception rate in each group during the first estrous cycle after the last PGF& injection was determined by counting the parturition date. The results of the experiment showed that the hgher the number ofovulating follicle the greater the percentage of ewes being pregnant (33,33, 63,12, 58,33, and 10%, for ewes having 1, 2, 3, and >3, ovulating follicle, respectively). It was suggested that an increasing number of ovulating follicle could be used to improve conception rate in ewes.